POTENCIALIDADES DAS TECNOLOGIAS DE INFORMAÇÃO E COMUNICAÇÃO COMO ALTERNATIVAS PARA O ENSINO DE GEOGRAFIA - Pereira, Thiago Barcelos (2021)
Information and communication technologies (ICTs) are part of the daily life of the vast majority of young students of Basic Education, thus becoming powerful possibilities for the teaching-learning process. In this sense, the present research proposes to